Huge Malignant Peripheral Nerve Sheath Tumors Originating In Neurofibromatosis Type 1 - Nabeela Riaz; Younas, Samreen (Journal of Rawalpindi Medical College, 2023)
Malignant peripheral nerve sheath tumors (MPNST) are malignant soft tissue neoplasms which account for 2% of all soft tissue sarcomas. These tumors are associated with poor prognosis, propensity to metastasize and high recurrence rates. About half of the MPNST arise from pre-existing neurofibroma and are associated with Neurofibromatosis type I (NF1), 10% are radiotherapy induced others are sporadic. Pathogenesis of MPNST is not fully understood yet. MPNST are common in extremities followed by trunk but are less common in head and neck area. MPNST show limited sensitivity to radiotherapy and chemotherapy and wide surgical resection is mainstay of treatment. We present a series of 3 cases of MPNST of head and neck region originating in patients having NF1.